Randomised controlled trial for high-dose intravenous zinc as adjunctive therapy in SARS-CoV-2 (COVID-19) positive critically ill patients: trial protocol. Issue 12 (2nd December 2020) - Perera, Marlon; El Khoury, John; Chinni, Vidyasagar; Bolton, Damien; Qu, Liang; Johnson, Paul; Trubiano, Jason; McDonald, Christine F; Jones, Daryl; Bellomo, Rinaldo; Patel, Oneel; Ischia, Joseph
Abstract : Introduction: SARS-CoV-2 (COVID-19) has caused an international pandemic of respiratory illness, resulting in significant healthcare and economic turmoil. To date, no robust vaccine or treatment has been identified. Elemental zinc has previously been demonstrated to have beneficial effects on coronaviruses and other viral respiratory infections due to its effect on RNA polymerase. Additionally, zinc has well-demonstrated protective effects against hypoxic injury—a clear mechanism of end-organ injury in respiratory distress syndrome. We aimed to assess the effect of high-dose intravenous zinc (HDIVZn) on SARS-CoV-2 infection. The end of study analyses will evaluate the reduction of impact of oxygen saturations or requirement of oxygen supplementation. Methods and analysis: We designed a double-blind randomised controlled trial of daily HDIVZn (0.5 mg/kg) versus placebo. Primary outcome measures are lowest oxygen saturation (or greatest level of supplemental oxygenation) for non-ventilated patients and worst PaO2 /FiO2 for ventilated patients. Following power calculations, 60 hospitalised patients and 100 ventilated patients will be recruited to demonstrate a 20% difference. The duration of follow-up is up to the point of discharge. Ethics and dissemination: Ethical approval was obtained through the independent Human Research Ethics Committee. Participant recruitment will commence in May 2020. Results will be published in peer-reviewed medical journals. Trial registration number: ACTRN126200000454976.